The impact of the COVID-19 pandemic on diabetic ketoacidosis admissions to a COVID-19-free hospital - Alnuaimi, Mouza; Siddiqua, Amatur; Aljaberi, Asma; Alkaabi, Juma; Aldahmani, Khaled; Afandi, Bachar; Almazrouei, Raya (Journal of Diabetes and Endocrine Practice, 2021)
Background: COVID19 infection is associated with worse outcomes in patients admitted with diabetic ketoacidosis (DKA). The indirect impact of the pandemic on DKA admissions to COVID19 free hospitals has not been evaluated. In this study, we evaluate the characteristics and outcomes of DKA admissions before and during the pandemic. Materials and Methods: This retrospective study included 146 episodes of DKA for patients aged 16 years and above admitted to Tawam Hospital, A COVID-19-free hospital, between April and October from 2017 to 2020. Sociodemographic, clinical, and laboratory data were retrieved from the electronic records. Data from the (2017–2019) period were compared to those during the COVID19 pandemic in 2020. Results: We evaluated 79 pre-COVID19 and 67 during the COVID19 admissions. During the pandemic, patients were older (30 vs. 23 years, P 0.2) with higher proportions of male sex (66% vs. 25%) and non-Emirati nationals (Arabs 17.9% vs. 12.7% and South Asian 20.9% vs. 3.8%). In addition, only 64.2% of patients had medical coverage compared to 92.4% in pre-COVID19 time. More patients with newly diagnosed diabetes (25.4% vs. 7.6%) and type 2 diabetes mellitus (32.8% vs. 17.7%) were encountered during the pandemic. Overall, there was no significant difference in severity, time to resolution, and mortality. Length of stay was longer for DKA admissions during the pandemic (4 vs. 3 days). Conclusion: In our COVID19-free hospital, the pandemic has led to an increased rate of DKA admissions and significant change in the sociodemographic characteristics of patients with DKA. Clinical care, patients' management, and outcomes were not adversely affected. Assessing the indirect impact of the pandemic is essential for future service planning.
Keywords: COVID1-9; diabetes; ketoacidosis; pandemic